Melanosis of the uterine cervix: a case report and literature review - Daniel Chang; Gerusa Biagione Tiburzio (Sociedade Brasileira de Patologia Clínica, 2013)
Melanosis of the uterine cervix is an extremely rare melanocytic lesion and should be differentiated from melanoma. It is a melanocytic hyperpigmentation of basal layer cells from the squamous mucosa of the uterine cervix without an increase in the number of melanocytes. We present a typical case of this entity. Furthermore, we discuss the possible origins of melanocytes in this region and their association with Laugier-Hunziker syndrome and Carney complex.